2011
DOI: 10.1016/j.ejcts.2011.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index predicts new-onset atrial fibrillation after cardiac surgery

Abstract: Body mass index, age, undergoing valve surgery and male gender, are independent risk factors for POAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Obesity has been related to early POAF, 19 particularly in patients >50 years of age 20 and in different surgical groups of both sexes. 22 In the Bramer et al study, only women with morbid obesity were at increased risk of POAF, although after adjustment for age, BMI was significantly associated with POAF in both sexes, but with weak OR. 22 These data have been summarized in a recent metaanalysis by Hernandez et al, which found a 12% increase in POAF in obese patients, compared to the non-obese patients.…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity has been related to early POAF, 19 particularly in patients >50 years of age 20 and in different surgical groups of both sexes. 22 In the Bramer et al study, only women with morbid obesity were at increased risk of POAF, although after adjustment for age, BMI was significantly associated with POAF in both sexes, but with weak OR. 22 These data have been summarized in a recent metaanalysis by Hernandez et al, which found a 12% increase in POAF in obese patients, compared to the non-obese patients.…”
Section: Study Limitationsmentioning
confidence: 99%
“…22 In the Bramer et al study, only women with morbid obesity were at increased risk of POAF, although after adjustment for age, BMI was significantly associated with POAF in both sexes, but with weak OR. 22 These data have been summarized in a recent metaanalysis by Hernandez et al, which found a 12% increase in POAF in obese patients, compared to the non-obese patients. 30 The present subjects had a lower incidence of obesity (17%) than that reported in that meta-analysis (42%).…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced age is the most consistent predisposing factor, with a 75% increase in the risk of developing POAF per decade. 6 Recent studies have implicated increased body mass index, prolonged ventilation, 7 and perioperative inflammation as additional risk factors. 2,6,8,9 Although there has been extensive research into the cause of POAF, mechanisms are still poorly understood.…”
mentioning
confidence: 99%
“…Moreover, some found BMI to be an independent predictor for new-onset AF in the general population. 21 Studies found that obesity, age and male gender to be independent predictors of post-operative AF. 13,14,15 Similarly in our study, we have observed the preoperative obesity (body mass index >30 kg/m2) in which there were 24.7% patients having obesity.…”
mentioning
confidence: 99%